Assessment of Nursery Administration and Identification of OrnamentalPlant Species: A Case Study of Tehsil Pattoki (Pakistan) (Journal of Asian Development Studies, 2023)
Regarding the spread of plants and how people might use urban biodiversity, nursery managementis essential for supplying resources for healthy plants. The current survey was conducted atMadina Nurseries in Pattoki, Punjab province, Pakistan. The current state of affairs, variedmanagement techniques used by gardeners to run their nurseries, and the spread of different typesof decorative plants served as the foundation for this survey. The main goals of this study were toenhance the present condition of nurseries and offer recommendations on the issues highlighted.Several characteristics include plant identification, nursery size, soil type, irrigation system,weeding, fertilizer usage, and propagation technique, respectively. The right fertilizer has to beutilized at the right time for plant growth and nurseries to flourish. It was acknowledged that theunidentified diseases and production of high-quality plants are associated with germplasm unitfacilities.